2020
DOI: 10.4274/jpr.galenos.2019.24650
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Artificial Neural Networks for Differential Diagnosis between Vesicoureteral Reflux and Urinary Tract Infection in Children

Abstract: Vesicoureteral reflux (VUR) and urinary tract infection (UTI) are common problems in children. Our goal is to use different models for the clinical decision of differential diagnosis of VUR and UTI in children. Materials and Methods: This was a retrospective cross-sectional study with 611 pediatric patients enrolled. Detailed information for the patients was obtained from hospital records and patient files. Three models including different variables were evaluated via an artificial neural network for the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The conversion of records into data was carried out by pediatric nephrologists in the research study team, and a database was created by the same team. Therefore, data collection and database have a consistent information [ 28 ]. The variables determined by the nephrologists for the study were presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The conversion of records into data was carried out by pediatric nephrologists in the research study team, and a database was created by the same team. Therefore, data collection and database have a consistent information [ 28 ]. The variables determined by the nephrologists for the study were presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The dataset contains 611 children out of which 425 are VUR and the remaining 186 are suffering with UTI. Results reveal that model 1 and 2 has a sensitivity of 0.682 and 0.852 while the results provided by model 3 having a sensitivity value of 0.939 for diagnosis of differential VUR and UTI 88 are the most optimal. Erogul et al, 89 on the other hand, have proposed an ANN‐based approach for the recognition of down syndrome in children.…”
Section: Applications Of Anns In the Field Of Medicinementioning
confidence: 98%
“…It is observed that most of the children suffering from recurrent urinary tract infection (UTI) have been diagnosed with Vesicoureteral reflux (VUR). We find an interesting technique that employs and analyzes three different models for which different variables are evaluated using ANN for diagnosis of VUR and recurrent UTI 88 . In the case of model 1, only clinical findings are used while model 2 contained laboratory findings too.…”
Section: Applications Of Anns In the Field Of Medicinementioning
confidence: 99%